PERUBAHAN KUALITAS HIDUP DAN KENYAMANAN SEHARI-HARI DENGAN SWISS BALL EXERCISE PADA SKOLIOSIS SEDANG - Fitriyani, Aris; Hartati, H; Handoyo, H (LPPM STIKES MUHAMMADIYAH GOMBONG, 2016)
Scoliosis is a disorder of the spine in the form of abnormal lateral curvature, it can occur in one or more vertebral regions. Approximately, 4% of all aged 10-14 years experience scoliosis. Therefore, it is necessary to act to reduce the degree of scoliosis therapy. This study aimed to determine the influence of the Swiss Ball Exercise (SBE) to decrease the degree of light idiopathic scoliosis and the quality of life as well as everyday comfort in aged 6-25 years.Type of quasi-experimental research or quasy experiment with pre-experimental design pre post test one group design is equipped with in-depth interviews at 3 participants. The total sample of 24 respondents gets Swiss ball exercise. This research was conducted at RSOP in 2014. The analysis used was Wilcoxon test.The results of the study 37.3% aged 19-25 years and 91.7% were female. The degree of scoliosis before SBE 91.7% had 21-40 degrees. After SBE forÂ 3 months did not occur difference in the degree of scoliosis but there were improvements in the quality and comfort of the everyday that is not rigid, reduced pain, feeling stronger / not easy to accomplish, and more healthy so be able to do daily activities well and tolerance due to the pull curvature of the spine.It can be concluded that SBE is effective for improvement of quality of life and everyday comfort at moderate scoliosis and reduce the degree of scoliosis <21, a mild degree. Keywords: Swiss ball exercise, Degree of Scoliosis